Gaming in the eyes of Portuguese society: An exploratory study - morais, A.; Oliveira, A. (ICERI2020 Proceedings, 2020)
Every day we see new technologies appearing and taking their place in society, with countless possibilities of using technology, whether as support for professional or leisure activities. Gaming is one of those possibilities, at the leisure level, in which we can enter a completely virtual world, “diving” into a video game and abstracting ourselves from the real world that surrounds us. Although this activity is of great adherence, there are divergent opinions regarding the consequences that may result from it and the purposes this activity can serve - such as the example of using gaming in teaching. An exploratory study was conducted through individual interviews with 6 individuals, aged between 20 and 52 years old, and with different, if any, contact with this activity. This study aims, in particular, to understand the perspective of Portuguese adults regarding gaming and what potential they associate to gaming activities as possible teaching tools. The data obtained from the interviews was analyzed using online content analysis software - the Leximancer platform. Concepts such as impacts on gaming, gaming on teaching and attitudes towards life merged out of this analysis. Participants consider that gaming is not just a useful way for fun and relaxation, but also a good stimulus and facilitator for learning. Although they consider that there are some negative points in gaming, such as increased aggression by those who play more violent games, or even a possibility of practice becoming addictive, they tend to have a positive opinion on gaming if used with limits. The items and concepts considered were also used to develop a questionnaire, answered by a population of Portuguese adults, in a subsequent study.